Fragilisation et modification des formations littorales meubles sur l’île d’Anjouan (Comores) : Quand l’érosion d'origine anthropique se conjugue au changement climatique - Kamardine Sinane; Gilbert David; Gwenaëlle Pennober; Roland Troadec (VertigO)
In Anjouan, Comoros islands, the first beach profiles surveys carried out during the period between 2008 and 2009 show two types of shapes : convex and concave. These beach profiles shapes are due to hydrodynamics forces and sand mining. Sand mining is more important in concave beach shapes profiles than in convex ones.Erosion caused by sand mining is confused with climate change impacts. This situation leads officials, with the support of the international community, to build seawalls to protect populations and infrastructures. However, this choice can widespread coastal erosion and contrasts with sand beach miner perception. For them, dealing with widespread coastal erosion must take into account undergoing social issues.